Digital Nativity, Computer Self-Efficacy, and Technology Adoption: A Study Among University Faculties in China - Zhao, Chen; Zhao, Lei (Frontiers in Psychology, 2021)
Technology acceptance and usage become obligatory for people when their work modes change as a result of an unexpected but irresistible force. This is especially true for teachers who are reluctant technology adopters compared with their students. During the COVID-19 pandemic, the Chinese government issued national policies to enforce online teaching and learning. As the success of online teaching largely depends on university faculties’ readiness and intentions, how they perceive and practice technology adoption becomes an issue that warrants in-depth research. Unlike their students who grow up with technology and can be seen as digital natives, university faculties may lack competence in using technology, whether to teach or do other tasks. Previous studies on faculties’ technology adoption were all conducted in situations where they made volitional decisions to use technology, but their mandatory technology use received scant attention. In addition, although studies suggested that teachers demonstrated features of digital natives, it remains unknown whether or to what extent their digital nativity correlates with technology intentions. To address these research gaps, the current study examined Chinese university faculties’ intentions to use technology for online teaching by incorporating digital nativity and computer self-efficacy as key determinants into technology acceptance variables. Results suggested that digital nativity was a key factor that affected university faculties’ online teaching, as evidenced by the fact that 67% of the variance could be explained by perceived usefulness, attitudes and digital nativity. In addition, it was also found that computer efficacy significantly influenced perceived ease of use.